Vous êtes sur la page 1sur 5

# 1.

## 2x2 +7x +6 = (x + 2)(2x + 3)

M1 A1

3x 2
7(3 + 2 x)

( 2 + x)(3 + 2 x)
3x 5

7
3
= ( 2 + x) x
some correct algebraic cancelling
4

M1 A1
[4]

2.

x2 9 = (x 3)(x + 3) seen

B1

## Attempt at forming single fraction

2 x 2 + 10 x + 12
x ( x 3) + ( x + 12)( x + 1)
( x + 1)( x + 3)( x 3) ; = ( x + 1)( x + 3)( x 3)
2( x + 2)( x + 3)
(
x
+ 1)( x + 3)( x 3)
Factorising numerator =
2( x + 2)
or equivalent = ( x + 1)( x 3)

M1; A1

M1 M1 A1
[6]

3.

(a)

(b)

2
13
+
x 3 ( x 3)( x + 7)
2( x + 7) + 13
2 x + 27
=
= ( x 3)( x + 7) ( x 3)( x + 7)
2x + 27 = x2 + 4x 21
x2 + 2x 48 = (x + 8)(x 6) = 0
x = 8, 6

M1
M1 A1

M1
M1 A1

3
[6]

## Holland Park School

4.

(a)

( x 3)( x + 2) ( x + 2)
2
;=
or 1 +
x( x 3)
x
x

B1,B1,B1

B1 numerator, B1 denominator ;
(b)

( x + 2)
= x +1 x2 = 2
x

M1 A1ft

## M1 for equating f(x) to x + 1 and forming quadratic.

x= 2

A1

3
[6]

5.

(a)

(3 x 2) ( x 1) 3 x + 2
,
( x + 1)( x 1)
x +1

M1B1, A1

## M1 attempt to factorise numerator, usual rules

B1 factorising denominator seen anywhere in (a),
If factorisation of denom. not seen, correct answer implies B1
(b)

## Expressing over common denominator

3x + 2
x (3 x + 2) 1
1

=
x +1
x ( x + 1)
x ( x + 1)

M1

(3x 2 x 2) x ( x 1)

[Or Otherwise:

x ( x 2 1)

M1

3x 1
x

Al

3
[6

## Holland Park School

6.

x(2 x + 3)
6

(2 x + 3)( x 2) ( x 2)( x + 1)

B1, B1

x( x 1) 6
(
x
2)( x + 1)
=

M1 A1ft

( x + 3)( x 2)
= ( x 2)( x + 1)

M1 A1

x+3
= x +1

A1

Alternative 1:
2 x 2 + 3x
6
(2 x + 3)( x 2) ( x 2)( x + 1)

B1

(2 x 2 + 3x)( x + 1) 6(2 x + 3)
(2 x + 3)( x 2)( x + 1)
=

M1 A1ft

(2 x 3 + 5 x 2 9 x 18)
= (2 x + 3)( x 2)( x + 1)

A1

( x 2)(2 x 2 + 9 x + 9)
= (2 x + 3)( x 2)( x + 1)

M1

( x 2)(2 x + 3)( x + 3)
,= x + 3
(
2
x
+
3
)(
x

2
)(
x
+
1
)
x +1
=

## Holland Park School

A1, A1

Alternative 2:

2 x 2 + 3x
6
(2 x + 3)( x 2) ( x 2 x 2)
x( 2 x + 3 x)
2 6
(
2
x
+
3
)(
x

2
)
x x2
=

B1

x ( x 2 x 2) 6( x 2 )
x 3 x 2 2 x 6 x + 12
,
=
2
( x 2)( x 2 x 2)
= ( x 2)( x x 2)

M1 A1ft

x 3 x 2 8 x + 12
2
= ( x 2)( x x 2)

A1

( x 2)( x 2 + x 6)
2
= ( x 2)( x x 2)

M1

( x + 3)( x 2)
,= x + 3
(
x

2
)(
x
+
1
)
x +1
=

A1, A1
[7]

( x + 2) 2 ,3( x + 2) + 3
7.

(a)

( x + 2) 2
f(x) =
x 2 + 4 x + 4 3x 6 + 3 x 2 + x + 1
=
=
*
( x + 2) 2
( x + 2) 2

M1A1, A1
cso

A1

M1A1, A1

(b)

1
3

x+ + ,> 0
2
4
x2 +x + 1 =
for all values of x.

Alternative
d 2
1
3
( x + x + 1) = 2 x + 1 = 0 x = x 2 + x + 1 =
dx
2
4

M1A1

## A parabola with positive coefficient of x has a minimum

x2 + x +1 > 0
Accept equivalent arguments

## Holland Park School

A1

(c)

1
3

x+ +
2
4

2
f(x) = ( x + 2)
Numerator is positive from (b)
x 2 (x + 2)2 > 0 (Denominator is positive)
Hence f(x) > 0

B1

1
[8]

8.
x2 1

2x4
2x4

-1
2x2
2
3x + x +1
- 2x2
x2 + x +1
x2
+1
x

a = 2 stated or implied
c = 1 stated or implied
2x 2 1 +

M1
A1
A1

x
2

x 1
a = 2, b = 0, c = 1, d = 1, e = 0
d = 1 and b = 0, e = 0 stated or implied

A1
[4]